Pengaruh Motivasi Belanja Hedonis dan Flash Sale Terhadap Impulsive Buying di Shopee Pada Siswa/i SMA Bina Warga 1 Palembang - Nurmila Sari, Ririn; Endah Dewi Purnamasari; Meilin Veronica (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The study aims to analyze the influence of hedonistic shopping motivations and flash sales on impulsive buying among students of the 1st Palembang High School. This research method uses a quantitative approach by distributing a questionnaire to 130 respondents who are users of the Shopee application, namely students in the 12th grade of high school. The results of this study showed a value of 3,460 with a significance value of 0,001<0,05, whereas on the flash sale variable, the value of 4,546 with a significant value of 0,000<0,05 showed that the hedonic shopping motivation and flash sale hypothesis had a positive and significant influence on impulse buying. Based on the calculation of the determination coefficient (R2), it was known that the influence value of hedonic shopping motivation and flash sales on impulsive buying was 35.6%, and based on the F test calculation, the hypothesis was accepted if F-calculation > Ftable or 35.096 > 3.070. thus accepting the hypotheses of Ha, which means that hedonistic shopping motivations and flash sales have a joint effect on impulse buying, so it can be confirmed that hedonistic sales motivation has a positive influence and a significant effect on impulse buying in high school students.